On the Expression ĪDE in the Hittite Temple-Palace Administrative Texts - Vigo, Matteo (Antiguo Oriente, 2025)
Despite their concise structure, the so-called “temple-palace administrative texts” are a treasure trove of information crucial for comprehending various facets of the Hittite administration. James Burgin’s recent re-edition has brought their significance to the forefront, giving us a fresh perspective and new insights. At least five texts related to “temple-palace administrative corpus” share a unique and intriguing structure. These documents exhibit the peculiar repetition of a recapitulatory period (character X/Y ĪDE) after a list of objects and recipients. Burgin interprets this group of texts as “extramural allocations”, underscoring the transient nature of the recapitulative periods marked by the Akkadogram ĪDE. In this article, I intend to elucidate the ultimate meaning of the expression ĪDE within this context by comparing it with the same expression found in other Mesopotamian administrative texts. Through this analysis, I aim to demonstrate that these routine control operations reflect specific administrative processes that share a similar formulation in administrative texts from the Aegean area of the second millennium BC.